Performance Evaluation of ESP32-Based IoT Communication latency in an Assembly line Model - Mohammad Fauzan Aulialdi; Vina Sari Yosephine; Muhammad Amir Fajri; Haikal Kamil (Universitas Medan Area, 2026)
The development of Internet of Things (IoT) technology provides opportunities to support the digitalization of Micro, Small, and Medium Enterprises (MSMEs), particularly in monitoring systems and automated operational data recording. However, the performance of IoT-based monitoring systems is highly influenced by communication delays between edge devices and cloud services, making communication performance evaluation essential to ensure system reliability prior to practical deployment. This study aims to evaluate the communication performance of an ESP32-based IoT system connected to a cloud spreadsheet by analyzing data transmission delays in a four-station assembly line model representing MSME-scale production processes. The method used is an experimental approach with 30 trials conducted at each station equipped with infrared sensors, and time measurement using a stopwatch as a visual reference. The collected data were analyzed using average values, standard deviation, and the Three Sigma method to evaluate communication stability. The results show that the average data transmission delay is approximately 3 seconds, with variations remaining within the control limits, indicating that the system operates under stable (in-control) conditions. Differences in delay among the stations indicate the influence of network communication characteristics, including Wi-Fi connection quality, network traffic, and the HTTP communication protocol used for cloud transmission. These findings demonstrate that the proposed system provides sufficiently stable communication performance to support operational monitoring in MSMEs and can serve as a baseline for the future development of cloud-based monitoring systems toward digital twin implementation.